LITERATURE REVIEW : GAMBARAN KEPUASAN PASIEN DALAM PELAYANAN KEPERAWATAN DI RUMAH SAKIT - Aries Wahyuningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2020)
The unequal distribution of employment by level of education is a problem in itself. Most of the service institutions in Indonesia also have not developed a career path for nurses, so the pattern of reward and welfare of nurses will affect performance. Nursing services as health service providers so that satisfaction is the main goal in providing quality services. This study aims to explain the description of nursing service satisfaction based on a literature review. This research used literature study. The literature obtained from the use of PubMed, and Google Scholar and 10 literature reviews were analyzed by PICO. The results of the research from the literature review showed that 7 journals (70%) patients were less satisfied and only 3 journals (30%) patients were satisfied with nursing services based on Community Satisfaction Index standards of hospital. Patient Satisfaction in Nursing Services From various literature review results found that the majority stated that they were not satisfied with nursing services.